EFEKTIVITAS IMPLEMENTASI MANAJEMEN BERBASIS SEKOLAH (MBS) DALAM MENINGKATKAN MUTU PENDIDIKAN MELALUI ANALISIS SWOT DI SD NEGERI 4 SANUR - Ida Bagus Gede Surya Abadi; Chindytia; Ni Putu Ayu Bintang Sandra Dewi; Ni Wayan Ocha Amelia Indira Mahasuari (STKIP Subang, 2026)
This study aims to analyze the effectiveness of School-Based Management (SBM) implementation in improving educational quality at SD Negeri 4 Sanur through a SWOT analysis approach. The study was motivated by the importance of autonomous, participatory, transparent, and accountable school management in addressing the demands for educational quality improvement in the digital era. The research employed a qualitative descriptive method with a case study approach. Data were collected through observations, interviews, documentation, and analysis of school documents. The findings indicate that the implementation of SBM at SD Negeri 4 Sanur has been relatively effective, particularly in the areas of curriculum management, student affairs, facilities and infrastructure management, and financial administration. The school's strengths include the quality of its teaching staff, the democratic leadership of the principal, a conducive learning environment, and strong stakeholder support. However, several weaknesses were identified, including the suboptimal use of educational technology, limitations in special support services, and uneven professional development opportunities for teachers. The opportunities available to the school include parental support, government policies, and advancements in educational technology, while threats arise from competition among schools, changes in educational policies, and increasing public expectations regarding the quality of educational services. Based on the SWOT analysis, the implementation of SBM at SD Negeri 4 Sanur is considered effective in supporting educational quality improvement. Nevertheless, further enhancement is needed in the areas of instructional innovation, human resource development, and community partnerships to ensure sustainable educational quality improvement.